Induction of estrus and multiple ovulation by administration of cloprostenol and super-ov through intra-vulvo submucosal (IVSM) route and embryo transfer in Sahiwal cows - Mishra, U K; Mishra, O P (The Indian Journal of Animal Sciences, 2012)
Pure Sahiwal cows (28 : 18 elit donors, 10 recipients) were synchronized for estrus using normal (500 µg intramuscular im) and reduced dose (125µg ivsm) of cloprostenol (estrumate) injected twice 11 days apart. The percentage of estrus observed after first injection of 500 µg im and 125 µg ivsm cloprostenol was 42.85% and 35.71 % respectively. similarly after second injection it was 75.00% and 78.57%, respectively, suggesting that a 4-time reduced dose of cloprostenol given through ivsm route can be used for induction of estrus to that or normal dose with comparable results. Six donor cows in each 3 groups were superovulated with 50 NIII im (group A). 50 NIH ivsm (group B) and 24 NIH ivsm (group C) of super-ov (a purified gonadotropin). The mean ovulation/corpus luteum(CL) and mean transferable embryos in group 13 were significantly (P